Achieving a Domestic Consensus on Global Climate Change in the United States: Sine Qua Non to an Effective Global Response?. - Reifsnyder, Daniel. (2017)
Abstract: Many believe that solving global climate change has become mired in discord and controversy, and that the U.N. negotiations are hopelessly stuck. This study asks why that is and what can be done about it? It argues that the United States is an indispensable party but that the absence of a domestic consensus makes the United States reluctant to lead - and that this is a key reason for the impasse. The study then asks what does agenda setting theory tells us about the current debate over climate policy in the United States and what are the prospects for a major shift toward `whole of country' engagement? Finally, it asks what impact such a shift by the United States would have on the international negotiations and how quickly it might occur? To assess the current stalemate in the climate negotiations, this study surveys multiple suggestions in the literature about what is blocking progress, and how to move forward. Despite the merits of these ideas, it contends that there is a sine qua non without which little else matters but with which everything is possible. Interviews with senior climate negotiators from a broad cross section of developed and developing countries buttress this argument. The study explores the reasons for U.S. ambivalence through the lens of three theorists - John Kingdon, Frank Baumgartner and Bryan Jones, and Thomas Rochon - and considers how and when significant policy change may occur. Assuming it does, the study asks, "what then?" Returning to the interviews and the "impasse" literature, the dissertation considers the effect of U.S. domestic action on the negotiations. The study reaches six key findings: (1) the United States today can significantly shape the global response to climate change; (2) to play a lead role, significant and far-reaching U.S. domestic action is vital; (3) the United States has broad scope to decide what kind of action makes sense for it, but the impact will need to be viewed by others as significant, in line with the science and perceptions of the U.S. "fair share;" (4) a shift in American attitudes toward climate change is necessary and possible if leadership takes advantage of the next policy window, and creates an effective narrative that convinces the public and the Congress that action is essential; (5) U.S. domestic action is necessary but not sufficient to craft an effective global response that addresses some of the factors that have blocked an agreement thus far; and (6) even with U.S. action and engagement, the issue will be exceedingly difficult to resolve because of the widely varying circumstances and aspirations of the parties and the complexities of the current process.; Thesis (Ph.D.)--Tufts University, 2014.; Submitted to the Dept. of Diplomacy, History, and Politics.; Advisor: William Moomaw.; Committee: Andrew Hess, and William Martel.; Keywords: Climate change, International relations, and Political Science.